(3GdGbJUGO GdOhdj (B/s - (3HcQj, cGeds ((3dHfGf(B: s (3GdOGQ GdLGeYjI(B, s, 1988)
(3CSGS GdJLGQI GdOhdjI h TQhW GdJLGQI , ejRGf GdeOahYGJ h GdONd Gdbhej , Shb GdUQa GdGLfHj h GNJdGd ejRGf GdeOahYGJ , SjGSGJ ejRGf GdeOahYGJ , GdfXGe GdfbOj GdOhdj h GdJcGed GdGbJUGOj (B.s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs